Identification and Assessment of Soil Physical and Chemical Properties for Vanili Plants in North Tinangkung District, Banggai Islands Regency - Saipul Saikim; Hertasning Yatim; Hidayat Arismunandar Katili (Faculty of Agriculture, Tompotika Luwuk University, 2021)
Soil physical and chemical properties are the main factors that significantlyinfluence vanilla production. This study aimed to identify the soil’s physicaland chemical properties, determine the soil fertility status, and evaluate the soilsuitability for vanilla plants cultivated at three villages in Tinangkung UtaraDistrict. This research has been carried out at the long-term monoculture of thevanilla plantation. The soil fertility properties have determined based onphysical properties such as texture (pipete method) and chemical propertiessuch as pH, organic C content (Walkey and Black), P2O5 (olsen) and K2O(HCL25%), base saturation/KB dan cation exchange capacity/CEC ) NH4OAcpH7). The data then matched to PPT soil fertility and BBSDLP land evaluationcriteria for the vanilla plant. The result showed that the soil in the study sitehas clayey texture, neutral soil reaction, moderate KB and P2O5, and moderateto high CEC. On the other hand, the soil exhibited lower content of organic Cand K2O. Despite soil fertility status determined as low, the evaluation analysisresulted marginally suitable, which could be optimised to highly suitable.